ChemInform Abstract: A General Iodine‐Mediated Synthesis of Primary Sulfonamides from Thiols and Aqueous Ammonia. Issue 49 (17th November 2016) - Feng, Jian‐Bo; Wu, Xiao‐Feng
Abstract: An oxidative amination of sulfides by aqueous ammonia affords primary sulfonamides in moderate to good yields.